Pests of the Flower Garden - Sloderbeck, Phillip E. (My University, 2005)
This publication helps gardeners select insecticides for uses in flower gardens. It lists common pests and how to identify them.
EP126_2005-03
Keywords: EP126; Insects; Lawn and Garden; EP